Response of Fruit Body Assemblage Color Lightness to Macroclimate and Vegetation Cover - Oechler, Henrik; Krah, Franz-Sebastian (Frontiers in Ecology and Evolution, 2022)
Understanding how species relate mechanistically to their environment via traits is a central goal in ecology. Many macroecological rules were found for macroorganisms, however, whether they can explain microorganismal macroecological patterns still requires investigation. Further, whether macroecological rules are also applicable in microclimates is largely unexplored. Here we use fruit body-forming fungi to understand both aspects better. A recent study showed first evidence for the thermal-melanism hypothesis (Bogert’s rule) in fruit body-forming fungi and relied on a continental spatial scale with large grid size. At large spatial extent and grid sizes, other factors like dispersal limitation or local microclimatic variability might influence observed patterns besides the rule of interest. Therefore, we test fungal assemblage fruit body color lightness along a local elevational gradient (mean annual temperature gradient of 7°C) while considering the vegetation cover as a proxy for local variability in microclimate. Using multivariate linear modeling, we found that fungal fruiting assemblages are significantly darker at lower mean annual temperatures supporting the thermal-melanism hypothesis. Further, we found a non-significant trend of assemblage color lightness with vegetation cover. Our results support Bogert’s rule for microorganisms with macroclimate, which was also found for macroorganisms.